Validasi Lembar Kerja Peserta Didik (LKPD) Berbasis Pendekatan Metaphorical Thinking untuk Kemampuan Pemahaman Matematis Peserta Didik di kelas VIII SMP - Irma Yetti; Dona Afriyani (Edusainstika: Jurnal Pembelajaran MIPA, 2021)
The main problem in this study is the limited learning resources used by students to understand the material and the difficulties of students in understanding the concepts taught by the teacher. Even though in terms of the number of learning resources used are sufficient, these learning resources cannot fully support students in understanding mathematics material. In addition, in applying the concept, the teacher did not arrange the knowledge of students properly so that students had difficulty understanding mathematical concepts. The purpose of the research in general is to produce Student Worksheets (LKPD) based on the Metaphorical Thinking Approach to Improve the Mathematical Comprehension Ability of Class VIII Students at SMP N 2 Pariangan in understanding mathematical concepts and motivating students to obtain data on what are the characteristics of a student-based LKPD. The resulting metaphorical thinking approach has met the valid criteria. The type of research used is research and development with development according to Van Den Akker which consists of 3 stages, namely: (1) front analysis stage (front-back analysis), (2) prototype stage (prototype) and (3)) the assessment stage (assessment). The data collection technique used to determine validation is the validation sheet. While the instrument used was a product validation sheet. The results showed that the characteristics of the LKPD based on the metaphorical thinking approach that were designed were valid. The results obtained from the LKPD validity test were 79% valid.